[Natatorium and Crandall Gym] - John H. Klopp::::::photographer::: (1940)
On front: "Looking N.W. across intersection of Mt. San Luis Street and Cuesta Avenue into East elevation of Crandall Gym on right with South end of Administration Bldg. showing over roof of Crandall Gym."